Environmental Product and Ecolabelling Knowledge dalam Pembentukan Sikap Ramah Lingkungan - Amanda Hoei; Juanny Avelia; Christiana Yosevina; Antonius W. Sumarlin (Universitas Prasetiya Mulya, 2022)
Recently, people, especially generation Z, have begun to become aware of the negative impact the fashion industry has on the environment and feel responsible for this pollution. To overcome the negative impact of the fashion industry on the environment, consumers are starting to use eco-friendly clothing and moving to the slow fashion trend. The purpose of this research is to investigate the factors that can influence the purchase of eco-friendly clothing for Generation Z in Indonesia. The conceptual basis of this research is the knowledge-attitude-behavior model and attitude-behavior-context theory. The research methodology is in the form of quantitative where the researcher collects 281 questionnaire respondents, and the data is processed using the SPSS 26 and AMOS 26 programs. From this study, ecolabelling knowledge, environmental product knowledge, green trust, environmental concern, ecolabelling desire, and environmental attitude are factors that can affect the intention to buy eco-friendly clothes in generation Z in Indonesia.